Non-lightlike framed rectifying curves in Minkowski 3-space - Jiaqi Huang; Kaixin Yao; Donghe Pei (Electronic Research Archive)
In this paper, we define non-lightlike framed rectifying curves. They may have singularities. We give equivalent definitions and a construction method for non-lightlike framed rectifying curves. Moreover, we also study the relationship between the non-lightlike framed rectifying curves and the non-lightlike framed helices, as well as the properties of the centrode of non-lightlike framed rectifying curves.